I-index for quantifying an urban location's irreplaceability. (November 2021) - Wang, Xi; Chen, Jie; Pei, Tao; Song, Ci; Liu, Yaxi; Shu, Hua; Guo, Sihui; Chen, Xiao
Abstract: A location's irreplaceability refers to the degree of difficulty with which it can be replaced by other locations. For example, the irreplaceability of airports, hospitals, and ATMs varies, and that between hospitals is also different. They differ in both the number of users and the extent of service area. Quantifying the location's irreplaceability provides guidance for urban planning, such as siting of public resources. Existing methods for quantifying an urban location's irreplaceability do not consider human activity at the location, therefore the revealed irreplaceability may deviate from the resident's perceptions. To address this issue, we use origin-destination flows to reflect human activity. We propose a flow-based locational measure, I-index, to quantify the location's irreplaceability. It can be viewed as 'H-index of flow' where we regard locations as scientists, flows as papers. I-index of a location is the maximum value of i such that at least i flows with a length of at least α  ∗  i meters have reached this location, where α is the conversion factor that can be determined adaptively from the flow dataset. I-index elegantly combines the flow volume and length into a single value. The effectiveness of the I-index is validated by simulation experiments. Two case studies show that the hospital's irreplaceability strongly correlates with the hospital bypass behavior and locations with strongly mixed urban functions are more irreplaceable. The implications for urban planning are further discussed. Highlights: This study proposes a flow-based locational measure, named I-index, to quantify an urban location's irreplaceability. The I-index can identify socially irreplaceable urban locations in the resident's daily life. The I-index can simultaneously express the flow volume and flow lengths in a location using a single value. The hospital's irreplaceability strongly correlates with the hospital bypass behavior. Large transportation hubs such as airports are the most irreplaceable urban locations.